Trends of antibiotic use at the end-of-life of cancer and non-cancer decedents: a nationwide population-based longitudinal study (2006-2018) - Nak-Hyun Kim; Kyungdo Han; Eunjeong Ji; Soyeon Ahn; Yunsang Choi; Seong Jin Choi; Song Mi Moon; Kyoung-Ho Song; Eu Suk Kim; Hong Bin Kim (Cambridge University Press, 2024)
Abstract Objective: This study aimed to assess the actual burden of antibiotic use among end-of-life (EOL) patients in South Korea and to compare trends between cancer and non-cancer decedents. Design: Population-based mortality follow-back study. Setting: Data from the Korean National Health Insurance Database, covering the period from January1, 2006, to December 31, 2018, provided for research by the National Health Insurance Service (NHIS), were used. Participants: All decedents from 2006 to 2018 were included and categorized as cancer decedents or non-cancer decedents. Methods: Annual antibiotic consumption rates and prescription rates were calculated, and Poisson regression was used to estimate their trends. Results: Overall antibiotic consumption rates decreased slightly among decedents in their final month with a less pronounced annual decrease rate among cancer decedents compared to non-cancer decedents (0.4% vs 2.3% per year, P <.001). Over the study period, although narrow spectrum antibiotics were used less, utilization and prescription of broad-spectrum antibiotics steadily increased, and prescription rates were higher in cancer decedents compared to non-cancer controls. Specifically, carbapenem prescription rates increased from 5.6% to 18.5%, (RR 1.087, 95% CI 1.085-1.088, P <.001) in cancer decedents and from 2.9% to 13.2% (RR 1.115, 95% CI 1.113-1.116, P <.001) in non-cancer decedents. Conclusions: Our findings show that patients at the EOL, especially those with cancer, are increasingly and highly exposed to broad-spectrum antibiotics. Measures of antibiotic stewardship are required among this population.